2003
DOI: 10.1097/01.brs.0000096942.29660.b1
|View full text |Cite
|
Sign up to set email alerts
|

ISSLS Prize Winner: The Innervation of the Intervertebral Disc: A Quantitative Analysis

Abstract: The lumbar intervertebral disc has a meager innervation. This is concentrated in the perianular connective tissue and the central endplate. Although receptor threshold is more closely related to nociceptive function than innervation density, these findings have important implications for any treatment of discogenic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(90 citation statements)
references
References 20 publications
1
87
0
2
Order By: Relevance
“…16,34,35 In the normal IVD the sensory nerve fibers 16,35,88 and their accompanying blood vessels 112 are most dense posteriorly and anterior-laterally but are generally observed only to a depth of 3.5 mm from the periphery of the annulus. Interestingly, sensory information from these nerves travels in the sinuvertebral nerve to the spinal cord via 2 possible routes: segmentally through the adjacent dorsal root or extrasegmentally through the paravertebral sympathetic chain.…”
Section: The 4 Tissue Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…16,34,35 In the normal IVD the sensory nerve fibers 16,35,88 and their accompanying blood vessels 112 are most dense posteriorly and anterior-laterally but are generally observed only to a depth of 3.5 mm from the periphery of the annulus. Interestingly, sensory information from these nerves travels in the sinuvertebral nerve to the spinal cord via 2 possible routes: segmentally through the adjacent dorsal root or extrasegmentally through the paravertebral sympathetic chain.…”
Section: The 4 Tissue Layersmentioning
confidence: 99%
“…86,87 Because these tears occur in a region that contains pain receptors, it is conceivable that they may act to generate symptoms. 35 High-intensity T 2 signals near the outer margins of the annulus have been described as representing hemorrhage or edema that may be associated with these tears. 68, 91 The meaningfulness of this "high-intensity zone" (HIZ) (FIG-URE 7) has been extensively investigated and, while it is highly correlated with pain production during discography, 68,91 it is also commonly observed in asymptomatic individuals.…”
mentioning
confidence: 99%
“…67 The bony vertebral endplate has a similar density of innervation. 69 Pain provocation studies associate severe back pain with relatively innocuous mechanical stimulation of the outer posterior anulus and endplate. 70 Painful discs are always structurally disrupted 67 and show irregular stress concentrations.…”
Section: Discogenic Painmentioning
confidence: 99%
“…Additional studies have identified nerve fibres and blood vessels in the endplates and subchondral bone in degenerate discs suggesting that tissue repair may be associated with back pain [11,17].…”
mentioning
confidence: 99%